A1_3 The Penny’s Dropped - Wynn, Joshua; Edwards, Peter; Allen, Liam (Physics Special Topics, 2012)
This paper investigates the common myth of whether dropping a penny from the top of the empire state building could kill a person that it hits at the bottom. The paper deals with a standard sterling penny dropped from the 102nd floor of the empire state building at 381m above ground level. The penny would not be able to reach a sufficient speed to kill or badly injure anybody walking below but would certainly be painful.Â